“Green Human Resource Management practices in leading Indian Banks during Covid Pandemic” - Mishra, Sarthak; Rath, Dr. Namita (The journal of contemporary issues in business and government, 2021)
The primary focus of any business now is to make it sustainable by ensuring efficient use of resources and energy so as to protect the environment and enhance the productivity. Indian Banks being the prime movers of the country’s economy, have strategically adopted “Green Banking” and have re-oriented their human resources through“Green Human Resource Management” (GHRM) practices, along with the UN mandated sustainable development goals (SDGs) as their business model. Even though there is good progress in Green Banking in customer transactions, a lot of gap and scope exist in Green Human Resource Management practices. The utility of Green HRM was felt more during the current Covid Pandemic when digital banking and Work From Home(WFH) have become the new normal. The present study analyses these practices as adopted by the leading banks like State Bank of India, HDFC Bank and Axis Bank more particularly during the current pandemic and gives suggestions for further improvement in the Post Covid era.